VD_FINDINFO 5/2012/DCA vom 17. Januar 2012 - VD Tribunal cantonal (2012)
CONCURRENCE DÉLOYALE, MÉDIA, COMPARAISON DE PRIX, PUBLICITÉ COMPARATIVE | 2 LCD, 3 al. 1 let. a LCD, 3 al. 1 let. e LCD, 261 CPC (CH), 266 CPC (CH)